Fracture performance of externally FRP strengthened reinforced concrete beams mixed with rigid fibres - Syed Ibrahim Syed Muhammad; Kandasamy Selvaraj; Thivya Jagadeesan; Vijayaraghavan Jagadeesan (Građevinar)
In recent decades experimental investigations on fibre reinforced polymer (FRP) laminate-strengthened reinforced concrete (RC) beams have been extensively conducted. It has been found effective in flexural and shear strengthening perspectives. On the other hand, a primary problem frequently encountered in such technique is the separation of FRP laminate with the concrete bonded surface. Such failures are due to the formation of localized flexural and otherwise shear cracks in the fragile region of the FRP-concrete interface. The debonding occurrence also significantly affects the strength enhancement of the laminated beams. The emphasis of the study is to enhance the potential performance of externally FRP strengthened RC beams by incorporating an effective crack controlling agent, that is ‘rigid hooked-end steel fibres’ in the matrix. Nine RC beams were cast and tested in this study with variables including different quantities of hooked-ends steel and glass fibre reinforced polymer (GFRP) thickness. The pre-cracking and post-cracking behaviour of the externally FRP strengthened RC beams mixed with the short fibres were systematically evaluated and improved performance at various stages of cracking was found. Another finding is the transformation of failure pattern from brittle to ductile due to exceptional strain-hardening phenomenon caused by steel fibres in the strengthened RC beams, in comparison to that of other beams without steel fibres. The formations and propagations of the cracks at different stages were numerically modelled for all the beams using the ANSYS and compared the numerical design validation with the experiment.